2013
DOI: 10.1186/2052-336x-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a new measure for assessing self-efficacy in response to air pollution hazards for pregnant women

Abstract: A self-efficacy instrument should be condition-specific. There are several instruments for measuring self-efficacy, but none are air pollution-specific. This study aimed to develop a self-efficacy measure for assessing pregnant women’s responses to air pollution hazards. A random sample of pregnant women aged between 18 and 35 years attending three prenatal care centers were entered into the study. Prenatal care centers randomly selected from a list of centers located in different geographical regions of Tehra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Air pollution is a serious threat to the health of pregnant mothers, and studies have shown the relationship between increased concentrations of carbon monoxide in environment and miscarried pregnancies. ( 1 , 10 ). Studies also suggest a relationship between air pollution and pregnancy outcome such as low birth weight and gestational age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollution is a serious threat to the health of pregnant mothers, and studies have shown the relationship between increased concentrations of carbon monoxide in environment and miscarried pregnancies. ( 1 , 10 ). Studies also suggest a relationship between air pollution and pregnancy outcome such as low birth weight and gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution is one of the most important problems of metropolitan cities. Caused by emissions of particulate matter, chemical, and biological materials, air pollution seriously threatens the health status of the residents of these regions and causes a variety of acute and chronic diseases ( 1 , 2 ). The amount of air pollution in some cities of regions such as China, Italy, Canada, and Japan has been reported beyond the threshold of permissible limit ( 3 – 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers were limited to collecting required data to view and complete checklists, so the ndings were just reported by elderlies; thus, the ndings might be affected by recall bias. However, according to previous research, self-reporting id considered, as a common way to evaluate performance in the behavioral sciences (18,28,(53)(54)(55). Given that the adult education approach has been used in a limited number of studies, the discussion of the results are limited in scope.…”
Section: Discussionmentioning
confidence: 99%
“…This model is speci cally tailored for prevention-based interventions as well as interventions that make short-term changes (29). The validity of this questionnaire was evaluated by the following method (30,31).…”
Section: Validitymentioning
confidence: 99%
“…This model is particularly suited for prevention-based interventions as well as relatively short-term interventions to achieve detailed changes [27]. Validity of the instrument was assessed through the following method [28,29].…”
Section: Validitymentioning
confidence: 99%